2010
DOI: 10.3354/aei00013
|View full text |Cite
|
Sign up to set email alerts
|

Reduced migratory performance of farmed Atlantic salmon post-smolts from a simulated escape during autumn

Abstract: Escape of migratory finfish species from fish farms, such as Atlantic salmon Salmo salar L., offer a challenge when considering the environmental risks of cage culture. The migratory behaviour of groups of cultured salmon smolts and postsmolts after a simulated escape was studied in a small fjord from May to October using telemetry. Five groups of fish were released approximately every 6 wk from mid-May to late October, each of them composed of 15 to 20 fish equipped with acoustic transmitters and 1780 to 3700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 42 publications
5
49
2
Order By: Relevance
“…Just over half of the tagged fish went out towards the open ocean, not following the in-migrating wild sal mon in the fjord at the same time. The leading hypothesis for the random dispersal of escaped adult farmed salmon is that the migratory performance of cage-reared salmon declines during the post-smolt stage at the end of their first summer in net pens (Skilbrei 2010). Another influence may be the fact that the hatcheries and smolt-rearing areas of the experimental fish were in another fjord system, which may affect their imprinting and migratory instincts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Just over half of the tagged fish went out towards the open ocean, not following the in-migrating wild sal mon in the fjord at the same time. The leading hypothesis for the random dispersal of escaped adult farmed salmon is that the migratory performance of cage-reared salmon declines during the post-smolt stage at the end of their first summer in net pens (Skilbrei 2010). Another influence may be the fact that the hatcheries and smolt-rearing areas of the experimental fish were in another fjord system, which may affect their imprinting and migratory instincts.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy included (1) mandatory reporting, (2) mechanisms to analyse and learn from the reporting, (3) cause assessments, (4) technical standards for equipment coupled with independent en forcement and (5) mandatory training of fish-farm staff. Skilbrei (2010) suggested that the prevention of escapes during the first marine summer should be a top priority, as the migratory ability of post-smolts was well developed until at least 6 wk following transfer to sea cages in May, whereupon their dispersal rates declined and chances of recapture increased. Other ideas, including the sterilization ) and conditioning of farmed fish (Tlusty et al 2008), may also reduce the risk of negative effects on wild stocks in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fork length of all fish and weight of samples were recorded. In addition, a small number of salmon were equipped with 9 mm telemetry transmitters for studies of migratory behavior (Skilbrei 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The target area chosen was Masfjorden, Western Norway. This is a well controlled area with respect to fish farming activity and fishing efforts, and where migratory behavior of released farmed fish is well documented (Skilbrei 2010).…”
Section: Introductionmentioning
confidence: 99%